Ketahanan Nasional: Tantangan di Dunia Pendidikan - Masnuna, Fatya Jauharotul (Maliki Interdisciplinary Journal, 2025)
This research aims to identify the challenges of national resilience in education. Through a literature study and literature study, it was found that the challenges of national resilience in the field of education are gaps in access and quality of education, lack of interest in literacy, lack of character values, and expensive education costs. The results of this study provide strategies to overcome the challenges faced by national resilience in the field of education.